How a sample of English stop smoking services and vape shops adapted during the early COVID-19 pandemic: a mixed-methods cross-sectional survey - Sharon Cox; Emma Ward; Louise Ross; Caitlin Notley (BMC, 2021)
Abstract Background The COVID-19 pandemic in England led to major changes in the delivery of support via stop smoking services (SSS) and to the widespread temporary closure of bricks and mortar e-cigarette retailers (vape shops herein). The impact of disruptions across the smoking cessation support landscape has not been fully documented. The purpose of this study was to capture how SSS and vape shops in England were affected and adapted their 'business as usual' during the early months of the COVID-19 pandemic. Method An online cross-sectional survey was conducted between March and July 2020. Surveys were disseminated through online networks, professional forums and contacts. Open-ended qualitative responses were coded using thematic analysis. Results Responses from 46 SSS and 59 vape shops were included. SSS were able to adapt during this period, e.g. offering a remote service. A high percentage (74.6%) of vape shops had to close and were unable to make changes; 71.2% reported business declining. For both vape shops and SSS qualitative data revealed practical challenges to adapting, but also new pathways to support and co-working. Conclusion The closure of vape shops appears to have most impacted smaller bricks and mortar shops affecting businesses by decline in customers and impacting staff (furlough). For those services that could stay open there may be lessons learned in how to support vulnerable and disadvantaged people who smoke by considering new pathways to support.